Does delivering chest compressions to patients who are not in cardiac arrest cause unintentional injury? A systematic review - Frances Williamson; Pek Jen Heng; Masashi Okubo; Abel Martinez Mejias; Wei-Tien Chang; Matthew Douma; Jestin Carlson; James Raitt; Therese Djärv (Resuscitation Plus)
Background: Chest compressions are life-saving in cardiac arrest but concern by layperson of causing unintentional injury to patients who are not in cardiac arrest may limit provision and therefore delay initiation when required. Aim: To perform a systematic review of the evidence to identify if; among patients not in cardiac arrest outside of a hospital, does provision of chest compressions from a layperson, compared to no use of chest compressions, worsen outcomes. Method: We searched Medline (Ovid), Web of Science Core Collection (clarivate) and Cinahl (Ebsco). Outcomes included survival with favourable neurological/functional outcome at discharge or 30 days; unintentional injury (e.g. rib fracture, bleeding); risk of injury (e.g. aspiration). ROBINS-I was used to assess for risk of bias. Grading of Recommendations, Assessment, Development and Evaluation methodology was used to determine the certainty of evidence. (PROSPERO registration number: CRD42023476764). Results: From 7832 screened references, five observational studies were included, totaling 1031 patients. No deaths directly attributable to chest compressions were reported, but 61 (6 %) died before discharge due to underlying conditions. In total, 9 (<1%) experienced injuries, including rib fractures and different internal bleedings, and 24 (2 %) reported symptoms such as chest pain. Evidence was of very low certainty due to risk of bias and imprecision. Conclusion: Patients initially receiving chest compressions by a layperson and who later were determined by health care professionals to not be in cardiac arrest rarely had injuries from chest compressions.